Edukasi dan Pelatihan Pemanfaatan Tanaman Obat Keluarga di Desa Dlingo Bantul sebagai Upaya Pencapaian Tujuan SDGs di Bidang Kesehatan: Education and Training on the Use of Family Medicinal Plants in Dlingo Village, Bantul, as an Initiative to Support the Achievement of Health-Related SDGs - Sukardiman, Sukardiman; Kusumawati, Idha; Handayani, Rosita; Sudjarwo, Sudjarwo; Munandar, Tristiana Erawati; Yusuf, Helmy; Diyah, Nuzul Wahyuning; Poerwono, Hadi; Purwanto, Bambang Tri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Global health issues have become increasingly urgent following the COVID-19 pandemic, which resulted in approximately 6.6 million deaths by 2022. This impact has prompted communities to revert to traditional medicines, aligning with the National Development Planning System (RPJPN) 2005-2025, which promotes a health paradigm through traditional remedies. Community service activities were carried out in partnership with the Ngudi Makmur Farmer Group (POKTAN) in Dlingo Village, Bantul Regency. The primary objective of this activity was to enhance residents’ knowledge in Dlingo Village regarding the benefits and processing of Family Medicinal Plants (TOGA). The methods employed included material development, counseling sessions, question-and-answer discussions, and direct practical training in the preparation of aromatherapy candles. Evaluation was undertaken using pretests and posttests, which demonstrated a significant increase in participants’ understanding. The average scores rose from 81.67 (pretest) to 132.5 (posttest), with a statistically significant difference (p <0.001). These findings indicate that the counseling was effective in improving knowledge about TOGA and its utilization in producing aromatherapy candles. Such activities not only enhance awareness but also reinforce community autonomy in managing traditional medicinal resources, in line with the health-related objectives of the Sustainable Development Goals (SDGs).